Absent Platelet Aggregation with Normal Fibrinogen Binding in Basset Hound Hereditary Thrombopathy - Patterson, Wayne R; Estry, Douglas W; Schwartz, Kenneth A; Borchert, Ronald D; Bell, Thomas G (Thrombosis and Haemostasis, 1989)
Platelets from dogs with Basset Hound Hereditary Thrombopathy (BHT) initially displayed a thrombasthenia-like aggregation defect but have been shown to have normal amounts of platelet membrane glycoproteins lib and Ilia (GPIIb-IIIa), and therefore are more accurately described as thrombopathic. The presence of normal quantities of GPIIb-IIIa, however, did not rule out the possibility of a functionally abnormal glycoprotein complex which would be unable to bind radio-labeled fibrinogen. Therefore, fibrinogen binding in BHT platelets was evaluated. Platelets from BHT and normal dogs were activated with 1 × 10−5 M ADP in the presence of 125I-fibrinogen and the surface-bound radioactivity was quantitated. The amount of fibrinogen bound by BHT dog platelets was not significantly different than that bound by normal dog platelets. Platelets from dogs with BHT bound 30,282 ± 3,133 and normal dog platelets bound 31,664 ± 2,772 molecules of fibrinogen per platelet. The quantitatively normal GPIIb-IIIa complex binds fibrinogen in normal amounts and does not seem to represent the abnormality responsible for the aggregation defect in BHT platelets. Therefore, other factors central to normal platelet function and related to platelet aggregation must be considered.
Keywords: Platelets; 125I-fibrinogen binding; Basset Hound Hereditary Thrombopathy; Platelet aggregation